2017
DOI: 10.1371/journal.pone.0175558
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin inhibits TNFα/IL-1α-induced CCL2 release through IKBK-epsilon signaling in MDA-MB-231 human breast cancer cells

Abstract: Mortality associated with breast cancer is attributable to aggressive metastasis, to which TNFα plays a central orchestrating role. TNFα acts on breast tumor TNF receptors evoking the release of chemotactic proteins (e.g. MCP-1/CCL2). These proteins direct inward infiltration/migration of tumor-associated macrophages (TAMs), tumor-associated neutrophils (TANs), myeloid-derived suppressor cells (MDSCs), T-regulatory cells (Tregs), T helper IL-17-producing cells (Th17s), metastasis-associated macrophages (MAMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 63 publications
(83 reference statements)
1
41
0
Order By: Relevance
“…A non-lethal working concentration in MDA-MB-231 cells was established for TNFα, apigenin (as previously reported) (22) and IL1α (Figure 1) where the sub-lethal working concentrations were set at the following: 40 μM apigenin and 40 ng/ml TNFα. To investigate TNFα-mediated induction of chemokines and the influence of apigenin, whole transcriptomic microarray analysis was conducted using the Affymetrix gene atlas system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-lethal working concentration in MDA-MB-231 cells was established for TNFα, apigenin (as previously reported) (22) and IL1α (Figure 1) where the sub-lethal working concentrations were set at the following: 40 μM apigenin and 40 ng/ml TNFα. To investigate TNFα-mediated induction of chemokines and the influence of apigenin, whole transcriptomic microarray analysis was conducted using the Affymetrix gene atlas system.…”
Section: Resultsmentioning
confidence: 99%
“…Apigenin is a natural compound which has the capacity to antagonize several mitigating events in human tumor development and tumor immune evasion. These include the capability to reduce inflammation, inhibit casein kinase 2 (CK2), matrix metalloproteinases 9 and 1, protein kinase C (18), cytochrome P450 1A1 (19) topoisomerase I (20) tumor growth factors (21), CCL2-induced release by TNFαactivated breast cancer (22) and blockade of drug resistanceassociated extrusion pumps (23,24). In the current study, we expand on our previous work by evaluating the effects of apigenin on TNFα-treated MDA-MB-231 cells (22) by analyzing the whole transcriptome.…”
mentioning
confidence: 99%
“…This gene also regulates survival signaling associated with NFκB pathway activation, enabling cell transformation [76,78]. Also, Bauer et al [79] studied the association between the IKBKE gene and CCL2 release, showing that IKBKE downregulation attenuates CCL2 expression in MDA-MB-231 TNBC cells. Likewise, the data from our previous study [80] demonstrated that the natural compound Plumbagin inhibited IKBKE gene expression and consequent release of CCL2 in TNF-α-induced MDA-MB-231 cells, strengthening the potential association between IKBKE and CCL2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of CCL2 by apigenin occurred through suppression of IKBKe signalling. [163][164][165][166][167][168][169][170][171][172] Apigenin overcame drug resistance and decreased colonization and cell growth in adriamycinresistant MCF-7 cells via downregulation of MDR1 and Pglycoprotein, as well as, suppression of STAT3 signalling and its nuclear translocation. The compound also diminished the secretion of MMP-9 and VEGF (STAT3 target genes) in these cells.…”
Section: Apigeninmentioning
confidence: 99%